The Effects of Covid-19 Pandemic on Family Stability in Ntungamo Sub-county Ntungamo District. - Nasasira, Kennedy (Kabale University, 2024)
COVID-19 was been declared a global pandemic virus outbreak on March 11, 2020, by WHO. It was also declared a pandemic in Uganda on 20" March 2020. The COVID-19 global pandemic has brought many challenges to people's lives including quarantine and other social distancing measures put in place to prevent the rapid spread of infection and serious illness or death. The purpose of the study was to examine the effects of covid-19 pandemic on the family stability in Ntungamo District.